Economic appraisal of Kinnow production in Sirsa district of Haryana - KUMAR, RAJ; SUMIT, SUMIT; BISHNOI, DALIP KUMAR; KUMAR, AJAY (The Indian Journal of Agricultural Sciences, 2021)
An economic analysis of kinnow has been presented through studying their costs and returns. The present study was carried out during 2017-18 in Sirsa district of Haryana. A sample of 30 kinnow respondents was taken purposively from various villages in Mandi Dabwali block of Sirsa district of Haryana. The results of the study revealed that average first year establishment costs per hectare for kinnow has been worked out to be ₹127979. Whereas, per hectare per year returns from kinnow orchard have been worked out to be ₹272845. The economic viability of the kinnow fruit, mainly net present value, internal rate of return, benefit-cost ratio and payback period have been computed as ₹783243.67, (26.24%), 1:3.76 and 7 years, respectively. The findings of study revealed that kinnow growing is a step forwards the diversification and commercialization of agriculture in the state and it also helps in doubling the farmers' income. Keeping in view all the facts, there is need to develop early fruit bearing varieties of kinnow, timely supply of necessary inputs to make more profitable kinnow cultivation.